Bahasa Figuratif Dan Citraan Pada Kumpulan Puisi Diksi Para Pendendam Karya Badruddin EMCE Dan Implementasinya Pada Pembelajaran Bahasa Di SMA - Wijaya, Dhanu Widi, Prof. Dr. Ali Imron Al-Ma'ruf, M.Hum (2016)
This research has two major objectives proposed by the researcher, namely: (1) to describe the form, function, meaning of figurative language in poetry collection of Badruddin Emce's Diksi Para Pendendam and (2) to explain the implementation of figurative language of poetry collection of Badruddin Emce's Diksi Para Pendendam in language learning at Senior High School. This research uses descriptive qualitative. The data source that is obtained from of poetry collection of Badruddin Emce's Diksi Para Pendendam has total: 9 titles of poetry. Technique of collecting data is library technique. Technique of analyzing data that is used is semiotic model, namely perusal of heuristic and hermeneutic. The result of this research is (1) figurative language that is found in poetry collection of Badruddin Emce's Diksi Para Pendendam is figure of speech consists of allegory, personification, simile, association, hyperbole, pleonasm, parallelism, and rhetoric dominated by the figure of speech of personification; idiom is obtained four data; proverb is obtained two data; and the imagery that is namely sight, hearing, motion, labeling dominated by the imagery of sight and (2) The implementation of language learning can be used as teaching material that is suitable with criteria for teaching materials, namely (a) teaching materials should be appropriate to the curriculum so as to support the achievement of instructional, (b) teaching materials should be in accordance with the level of education and development of students in general, (c) teaching materials should be organized in a systematic and continuous, ( d) teaching materials should include things that are factual and conceptual. Keywords: Figurative Language, Imagery, Poetry Collection of Badruddin Emce's Diksi Para Pendendam, Language Learning at Senior High School.